Effect of Dialogue Focused Supervisory Relationship in Cross-ethnic Supervision to Enhance Midwifeâs Performance - Trisno, Idawati; Suhariadi, Fendy; Pudjirahardjo, Widodo J (Health Notions, 2017)
Midwifeâs performance at Primary Health Care (PHC) still not optimal, slacken the effort of reducing maternal death. Unavailability of doctor at  PHC placed greater responsibility on midwife, thus improving midwifeâs performance is crucial. Midwifeâs performance influenced by ability, motivation, and supervision. Cross- ethnic supervision combined with line manager supervision, fit in the development of dialogue focused supervisory relationship (DFSR) in midwifery supervision. This study aimed to analyse the effect of DFSR on midwifeâs performance, and the relationship between cross-ethnic supervision  and DFSR. This research used crosssectional design. Using random sampling techniques, 113 pairs of midwives -supervisors working in PHC at Kupang city and Kupang district were obtained. Data analysed using regression analysis. The findings were: (1) quality of DFSR affecting  midwifeâs performance improvement, with quality of dialogue give strongest influence, (2) good quality supervisory relationship decrease midwifeâs performance, and (3) cross-ethnic supervision didnât have significant relationship towards DFSR. The development of DFSR as a new construct and evident of the relationship between DFSR and midwifeâs performance is a novel in this study. To enrich this finding, future research should use longitudinal design and with different type of respondent. Study in exploring factor in cross-ethnic supervision that may influence DFSR also suggested.